Pseudoenantiomeric oxetane delta-amino acid scaffolds derived from L-rhamnose and D-xylose: D/L-alanine-D-serine and glycine-L-serine dipeptide isosteres - Johnson, S; Jenkinson, S; Angus, D; Jones, J; Watkin, D; Fleet, G (2004)
A series of oxetane δ-amino acid scaffolds derived from L-rhamnose and D-xylose provide a new class of templated sugar amino acids (SAA), which can be considered as D/L-alanine-D-serine and glycine-L-serine dipeptide isosteres. © 2004 Elsevier Ltd. All rights reserved.